Finite Element Analysis of Temperature Distribution and Stress Behavior of Squeeze Pressure Composites. (27th September 2021) - Gurusamy, P.; Sathish, T.; Mohanavel, V.; Karthick, Alagar; Ravichandran, M.; Nasif, Omaima; Alfarraj, Saleh; Manikandan, Velu; Prasath, S.
Abstract : Aluminium-reinforced composites play a vital role in the engineering industry because of their better strength and stiffness. The properties are directly related to the solidification phenomenon of the cast alloy. The design engineer should understand the importance of the solidification behavior of base alloy and its reinforcement. Composites' solidification study is rare, and the reviews are limited. The solidification process is analyzed using the finite element method (FEM), and this would fetch a lot of information about the cooling rate of the composites and also helps to reduce the time in experimentation. This paper reports and plots the cooling curves of Al/SiC p composites using simulation software. Cylindrical-shaped composites were developed using the squeeze casting method, and the experimental cooling curves were plotted using a K-type thermocouple. Composites samples were prepared at the following squeeze pressures: 0, 30, 50, 70, 100, and 130 MPa; melt and die temperature was kept constant at 800 and 400°C, respectively. The experimental and FEA cooling curves were compared, and it was agreed that the increase in the squeeze pressure increases the cooling rate of the developed composite. Furthermore, the effect of temperature distribution from the inner region of the melt and die material which causes the radial and tangential stress of components has also been examined.